2017
DOI: 10.1007/s00603-017-1355-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on the Influence of Artificially Altered Rock Mass Properties on Mechanical Excavation

Abstract: guaranteeing the access to mineral deposits and for extracting the valuable minerals from these deposits. Mechanical excavation tools like full-face tunnel boring machines and roadheaders use either discs or conical picks for applying the required forces into the rock mass. The efficiency of the processes is mainly governed by the mechanical properties of the rock type, especially strength and abrasivity. Roadheaders are limited by a uniaxial compressive strength of 150 MPa, TBMs by roughly 300 MPa. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…1(b)). Thus, the total energy consumption of digging is the sum of the energy consumption of cutting and the energy consumption of transporting the soil along the cut profile with its subsequent unloading onto the conveyor [3].…”
Section: Methodsmentioning
confidence: 99%
“…1(b)). Thus, the total energy consumption of digging is the sum of the energy consumption of cutting and the energy consumption of transporting the soil along the cut profile with its subsequent unloading onto the conveyor [3].…”
Section: Methodsmentioning
confidence: 99%
“…7 In recent years, many studies, which aimed to increase cutting performance and reduce cutting consumption by using the roadheaders more efficiently, have been conducted by different researchers. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Ramazan comakli et al deeply analyzed the influences of coal and rock properties on roadheader cutting load, and subjected different sandstones with uniaxial compressive strength to cutting tests under different levels of cutting parameters, and the change rule of roadheader cutting load under different coal rock properties is obtained. [8][9][10] K. Fukui et al suggested a method to estimate rock strength from the cutting force exerted by the roadheader, based on the results of laboratory experiments, which offers a basis for selection of cutting head with different geological conditions of coal or rock.…”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, many studies, which aimed to increase cutting performance and reduce cutting consumption by using the roadheaders more efficiently, have been conducted by different researchers. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Ramazan Comakli et al deeply analyzed the influences of coal and rock properties on roadheader cutting load and subjected different sandstones with uniaxial compressive strength to cutting tests under different levels of cutting parameters, and the change rule of roadheader cutting load under different coal rock properties is obtained. [6][7][8][9] H. Ergin et al established the mathematical model of the cutting system of longitudinal roadheader, and they obtained the threedimensional force of the cutting head.…”
Section: Introductionmentioning
confidence: 99%
“…The cutting head parameters are optimized and the cutting efficiency of the roadheader is improved by analyzing dynamic characteristics of roadheader cutting system. 19 Yang et al 20,21 put forward the method of using the shearer motor working parameters or the shearer rocker arm horizontal vibration signal to reflect the hardness of coal and rock. To the best of our knowledge, this method is mainly used to distinguish coal and rock interface of the shearer, and seldom applied in cutting rock hardness identification of roadheader.…”
Section: Introductionmentioning
confidence: 99%